Clinicopathological features and survival of gallbladder squamous cell carcinoma: analysis of 121 cases - Zou, Xiao-Ping (Int J Clin Exp Pathol, 2018)
Purpose: The aim of the present study is to promote deeper pathological and clinical understanding of gallbladder squamous cell carcinoma (GBSCC) and provide new evidence for its diagnosis and treatment. Methods: Two cases of GBSCC from the First Affiliated Hospital of Guangxi Medical University were collected. A comprehensive analysis was conducted based upon these 2 cases and another 119 GBSCC cases from the literature. Survival analysis was performed using the Kaplan-Meier method. Results: Among all the patients, GBSCC was frequently diagnosed in older women with a mean age of 62.8 years old. Abdominal pain was the most common symptom. The majority of GBSCC cases were combined with cholelithiasis. Keratinization was frequently observed microscopically. Among 90 cases with histology data, most showed high or, high-moderate differentiation (60%, 54/90). More cases were diagnosed in advanced TNM stages (85.4%, 82/96). In 73 cases, the follow-up time was 0.5-125 months, with a mean survival time 47.3 months and a median survival time of 12 months. Survival analysis indicated that patients with polypoid lesions (P = 0.047) and receiving R0 radical operation (P < 0.001) had better prognoses. Conclusion: Given the scarcity and implicit clinical manifestations of GBSCC, early diagnosis is challenging. The key to better survival is a radical operation with no remaining lesion.